2018
DOI: 10.1177/0310057x1804600110
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Simple Three-Level Bronchoscopic Assessment of Inhalation Injury to Predict in-Hospital Mortality and Duration of Mechanical Ventilation in Patients with Burns

Abstract: Major burn centres in Australia use bronchoscopy to assess severity of inhalation injuries despite limited evidence as to how best to classify severity of inhalational injury or its relationship to patient outcomes. All patients with burns who were admitted to the intensive care unit (ICU) at The Alfred Hospital between February 2010 and July 2014 and underwent bronchoscopy to assess inhalational injury, were reviewed. Age, total body surface area burnt, severity of illness indices and mechanisms of injury wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…These registries provided demographic data, including patient age and sex, mechanism of burn, date of injury, %TBSA burn, intensive care unit (ICU) length of stay, surgical management, and ventilation requirements. The presence and severity of inhalation injury was also extracted from the VABS database, and was diagnosed using a standardized bronchoscopy scoring system based on the abbreviated injury score, as previously reported [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…These registries provided demographic data, including patient age and sex, mechanism of burn, date of injury, %TBSA burn, intensive care unit (ICU) length of stay, surgical management, and ventilation requirements. The presence and severity of inhalation injury was also extracted from the VABS database, and was diagnosed using a standardized bronchoscopy scoring system based on the abbreviated injury score, as previously reported [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The place for bronchoscopy and broncho-alveolar lavage in the diagnosis and treatment of inhalational injury was also studied [31,32]. Bronchoscopy allows visualization of the upper airway and proximal parts of lower airways and may be useful in suctioning of debris.…”
Section: Management Of Inhalational Injuries and Acute Respiratory DImentioning
confidence: 99%
“…Bronchoscopy allows visualization of the upper airway and proximal parts of lower airways and may be useful in suctioning of debris. Studies have shown the correlation between bronchoscopy classification of severity of the inhalational injury and in-hospital mortality and duration of the mechanical ventilation [31]. In severe subglottic inhalational injuries, bronchoscopy and pulmonary toileting and nebulization using fibrinolytic and mucolytics were shown to be beneficial [32].…”
Section: Management Of Inhalational Injuries and Acute Respiratory DImentioning
confidence: 99%
“…This is important because inhalational injury confirmed by bronchoscopy and stratified by severity according to the Abbreviated Injury Score has been shown to predict inpatient mortality after a burn. 93 Regression models derived from data based on the clinical examination are used to predict clinical outcomes following a burn. Examples of scores derived from these models include the Baux score, 94 the Zawacki score, 95 the Abbreviated Burn Severity Index, 96 Roi's model, 97 and the Unit Burn Standard Index.…”
Section: The Clinical Assessment Of Patients With Severe Burnsmentioning
confidence: 99%